Efficiency of control of weeds in corn sowing at different systems of basic till of soil in Right-Bank Forest-Steppe of Ukraine - Танчик, С. П.; Миколенко, Я. (Scientific Progress & Innovations, 2016)
We investigated influence of Ploughing with gimbleting (ploughing), superficial, ploughing (without gimbleting) and «zero» tills of soil on a weediness groupment and productivity of corn for grain in Right-Bank Forest-Steppe of Ukraine. We fixed the best contamination of efficiency of ploughing without gimbleting till of soil, the lowest – at a zero till. The end of the growing season there was active growth weed component due to favourable terms (humidity, warmly), that substantially influenced on an amount and mass of weeds in sowing. The greatest productivity on the average value is fixed at ploughing without gimbleting till and it was 9,7 t/ga, the minimum is fixed at superficial till of soil and it was 8,8 t/ga.